Implementation of the Jigsaw Method in Improving Learning Outcomes of the Pillars of Islam and Pillars of Faith Material at SD Negeri 0404 Pasar Ujung Batu - Siregar, Siti Khodijah; Siregar, Lely Anni (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the application of the Jigsaw method in improving learning outcomes of the Pillars of Islam and Pillars of Faith material at SD Negeri 0404 Pasar Ujung Batu. The Jigsaw method is a cooperative learning model that emphasizes cooperation between students in understanding the material in depth. In this method, students are divided into small groups and each member is responsible for studying and explaining certain parts of the material to their group mates. This study uses a quantitative approach with a classroom action research (CAR) design which is carried out in two cycles. The subjects of the study were fourth grade students of SD Negeri 0404 Pasar Ujung Batu. Data were collected through learning outcome tests, observations, and interviews. The results showed that the application of the Jigsaw method can improve students' understanding of the Pillars of Islam and Pillars of Faith material. This can be seen from the increase in the average value of student learning outcomes from cycle I to cycle II. In addition, the Jigsaw method also contributes to increasing active student participation, training communication skills, and creating a more interactive and enjoyable learning environment. With increased learning outcomes and student involvement, the Jigsaw method can be used as an alternative effective learning strategy. These findings provide implications for teachers in developing innovative learning methods that can improve students' understanding, especially in Islamic Religious Education subjects in elementary schools.